2019
DOI: 10.1186/s12871-019-0743-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various dilute administration of rocuronium bromide on both vascular pain and pharmacologic onset: a randomized controlled trial

Abstract: Background Rocuronium bromide (RB) is known to cause vascular pain. Although there have been a few reports that diluted administration causes less vascular pain, there have been no studies investigating diluted administration and the onset time of muscle relaxation. Therefore, we examined the influence of diluted administration of RB on the onset time of muscle relaxation and vascular pain. Methods 39 patients were randomly assigned to three groups: RB stock solution 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The stimulation on chemoreceptors by the pH and osmotic pressure of the rocuronium solution can cause painful sensations at the injection site [ 9 ]. Kanazawa et al [ 10 ] discovered that diluted rocuronium is effective in alleviating injection pain when administered through dorsal digital veins, which indicated that rocuronium-induced injection pain might be related to the intensity of drug stimulation on the vessels’ wall. Furthermore, rocuronium may permeate through the vascular wall to surrounding tissues, promoting histamine to be released, and creating local swelling and pain, as well as stimulating local nerve terminals to induce signal transduction, and generating central pain perception [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation on chemoreceptors by the pH and osmotic pressure of the rocuronium solution can cause painful sensations at the injection site [ 9 ]. Kanazawa et al [ 10 ] discovered that diluted rocuronium is effective in alleviating injection pain when administered through dorsal digital veins, which indicated that rocuronium-induced injection pain might be related to the intensity of drug stimulation on the vessels’ wall. Furthermore, rocuronium may permeate through the vascular wall to surrounding tissues, promoting histamine to be released, and creating local swelling and pain, as well as stimulating local nerve terminals to induce signal transduction, and generating central pain perception [ 11 ].…”
Section: Discussionmentioning
confidence: 99%